CONCENTRATION OF BENZALKONIUM CHLORIDE IN DONAN RIVER CONTAMINATED WITH DOMESTIC WASTE - Ayu, Nurina; Rahayu, Nur Laila; Setyastuti, Aryanti Indah (AQUASAINS, 2024)
The distribution of benzalkonium chloride (BAC) in inland waters has not been widely studied, despite its known dangerous effects on organisms. This study was conducted to determine the concentration of BAC in the Donan River, Cilacap, which receives significant input from domestic waste, particularly from the food industry. The study employed a quantitative descriptive method to analyze the presence of BAC in the river, with sampling stations selected using the purposive sampling method to ensure comprehensive coverage. Samples were collected from five different stations along the Donan River, revealing BAC concentrations at station 1 ranging from 0.128 to 0.140 µg/l, station 2 from 0.213 to 0.237 µg/l, station 3 from 0.163 to 0.190 µg/l, station 4 from 0.176 to 0.210 µg/l, and station 5 from 0.240 to 0.247 µg/l. These findings indicate that the concentration of BAC in the Donan River is comparable to levels found in other rivers worldwide, where the presence of BAC has been documented. The study highlights the need for regular monitoring of BAC levels in inland waters, given its potential ecological impacts. The elevated levels of BAC, especially in areas receiving substantial domestic waste, suggest that the discharge from the food industry and other domestic sources significantly contributes to the contamination.  Keywords: domestic waste, ecology, micro pollutants, toxicology, water pollution.